Gene Expression Profiling in Multiple Myeloma: Redefining the Paradigm of Risk-Adapted Treatment - Cerchione, Claudio; Usmani, Saad Z.; Stewart, A. Keith; Kaiser, Martin; Rasche, Leo; Kortüm, Martin; Mateos, María-Victoria; Spencer, Andrew; Sonneveld, Pieter; Anderson, Kenneth C. (Frontiers in Oncology, 2022)
Multiple myeloma is a blood cancer characterized by clonal proliferation of plasma cells in the bone marrow. In recent years, several new drugs have been added to the therapeutic landscape of multiple myeloma, which have contributed to increased survival rates. However, while the use of therapeutics has evolved, there is still a group of high-risk patients who do not benefit from current treatment strategies. Risk stratification and risk-adapted treatment are crucial to identify the group of patients with urgent need for novel therapies. Gene expression profiling has been introduced as a tool for risk stratification in multiple myeloma based on the genetic make-up of myeloma cells. In this review we discuss the challenge of defining the high-risk multiple myeloma patient. We focus on the standardized analysis of myeloma cancer cells by gene expression profiling and describe how gene expression profiling provides additional insights for optimal risk-adapted treatment of patients suffering from multiple myeloma.